Phosphinic peptide inhibitors as tools in the study of the function of zinc metallopeptidases. (August 2000) - Dive, V.; Lucet-Levannier, K.; Georgiadis, D.; Cotton, J.; Vassiliou, S.; Cuniasse, P.; Yiotakis, A.
Abstract : The development of the combinatorial chemistry of phosphinic peptides has led to the discovery of both highly potent and selective inhibitors of various zinc metalloproteinases. Several properties of these compounds are reviewed, supporting the view that this class of inhibitors should represent useful tools for probing several aspects of the function of this broad family of proteases in vivo.